НАЛОГОВАЯ НАГРУЗКА КАК ЭКОНОМИЧЕСКИЙ ПОКАЗАТЕЛЬ, ХАРАКТЕРИЗУЮЩИЙ НАЛОГОВУЮ СИСТЕМУ ГОСУДАРСТВА - Ермекбаева, Б Ж; Тагайбекова, Н П; Мамишова, К С (Journal of Economic Research & Business Administration, 2015)
In article various techniques of definition of tax loading and degree of influence of these techniques on definition of a uniform methodological basis of calculation of tax burden are considered.